2019
DOI: 10.1371/journal.pntd.0007510
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Glossina fuscipes fuscipes to visually attractive stationary devices baited with 4-methylguaiacol and certain repellent compounds in waterbuck odour

Abstract: Background A blend of compounds (pentanoic acid, guaiacol, δ-octalactone and geranylacetone) identified in waterbuck ( Kobus defassa ) body odour referred to as waterbuck repellent compounds (WRC) and a synthetic repellent 4-methylguaiacol have previously been shown to repel tsetse flies from the morsitans group. However, these repellents have not been evaluated on palpalis group tsetse flies. In this study, we evaluated the effect of these repellents on catches of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…A four-component repellent blend identified from waterbuck, Kobus ellipsiprymnus defassa (waterbuck repellent compounds, WRC), comprising geranyl acetone, guaiacol, pentanoic acid and -octalactone embedded in repellent collars is currently being used to protect cattle against savannah tsetse flies in some parts of Kenya (Saini et al, 2017). Further field evaluation of the WRC on the riverine tsetse flies G. f. fuscipes, using traps and targets, has shown some promising results for the control of the vectors of the human-infective trypanosomes (Mbewe et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A four-component repellent blend identified from waterbuck, Kobus ellipsiprymnus defassa (waterbuck repellent compounds, WRC), comprising geranyl acetone, guaiacol, pentanoic acid and -octalactone embedded in repellent collars is currently being used to protect cattle against savannah tsetse flies in some parts of Kenya (Saini et al, 2017). Further field evaluation of the WRC on the riverine tsetse flies G. f. fuscipes, using traps and targets, has shown some promising results for the control of the vectors of the human-infective trypanosomes (Mbewe et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The size of the residue ellipse represents the strength of the contact. reduced trap catches by 33% and the different components had a different contribution to spatial repellency of the WRB (Mbewe et al, 2019). Our results show the additional effect of WRB as an antifeedant, besides on its spatial repellency.…”
Section: Discussionmentioning
confidence: 64%
“…Until recently, the main tools for tsetse control were odor-baited traps and targets (Kuzoe and Schofield, 2004). Additionally, recent use of the tsetse repellent blend (waterbuck repellent blend [WRB]) has reduced the transmission of animal trypanosomiasis in cattle by reducing contact between bloodseeking Glossina pallidipes and cattle hosts (Saini et al, 2017) and has been shown to reduce trap catches of Glossina fuscipes fuscipes (Mbewe et al, 2019). The cellular and molecular mechanisms of the spatial repellent odors are not well understood, yet such knowledge will enable us to improve the efficacy of the existing repellent blend or to identify novel repellents for control of various tsetse fly species of both medical and veterinary importance.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has only been used for extensive tsetse elimination in Zimbabwe and in the Zambian West Province because of the cost, the logistic requirements, and the need for government commitment [94]. Repellents can also be employed for vector control, for instance, the push-pull control method employs repellents to push the tsetse flies towards stationary visual attractants designed to kill the flies [98]. The repellent mix called waterbuck repellent compounds (WRC) and 4-methylguaiacol which were known Mortisan group tsetse fly repellents were tested for their effects on the Palpalis group and found to effectively repel Glossina fuscipes fuscipes [98].…”
Section: Vector Controlmentioning
confidence: 99%
“…Repellents can also be employed for vector control, for instance, the push-pull control method employs repellents to push the tsetse flies towards stationary visual attractants designed to kill the flies [98]. The repellent mix called waterbuck repellent compounds (WRC) and 4-methylguaiacol which were known Mortisan group tsetse fly repellents were tested for their effects on the Palpalis group and found to effectively repel Glossina fuscipes fuscipes [98]. Similarly, unrefined zebra skin odour, as well as a chemical mix with identical odor, was found to significantly repel Glossina pallidipes [99].…”
Section: Vector Controlmentioning
confidence: 99%